Numerical investigation of the effect of three types of spiral coils on the hydrothermal behavior of fluid flow in a shell and coil heat exchanger - Ahmed Mir; Seyed Hossein Hashemi Karouei; Rassol Hamed Rasheed; Pradeep Kumar Singh; Saurav Dixit; Rifaqat Ali; Walid Aich; Lioua Kolsi (Case Studies in Thermal Engineering)
This investigation is specifically centered on quantitatively assessing the heat transfer and fluid movement within a shell and spiral tube heat exchanger comprising three distinct designs. Water was considered as the heat transfer fluid, operating within the spiral coil and the shell. In this setup, the hot fluid circulates inside the coil while the cold fluid is contained within the shell. The research covers a range of Reynolds numbers from 500 to 2000 and is split into two parts. The first part of the study examines the impact of three different spiral coil models and evaluates their thermal performance. In the second part, the best spiral coil is selected based on the findings from the first part. Three different spiral winding pitches (P) are considered: 60 mm, 50 mm, and 40 mm, with the results compared to those of a simple winding. Among the three models analyzed in the first part, model (A) with a special helical coil design exhibited the greatest thermal productivity across different Reynolds numbers. Findings showed that the helical coil with the model (A) design enhances the energy exchange between hot and cold fluid particles owing to the reinforcement of centrifugal force, intensified secondary flow, and improved radial mixing of particles. As a result, this particular coil displayed significant thermal perform effectiveness because of the intensified vortex movement of liquid particles and the thinning of thermal boundary layers. The second part of the study revealed that the thermal performance of the spiral coil with a 60 mm pitch surpassed that of the other two models. At a Reynolds number of 500, it was observed that the thermal performance coefficient increased by 60 % for the model with a 60 mm pitch, 45 % for the model with a 50 mm pitch, and 28.8 % for the model with a 40 mm pitch. This indicates a significant improvement in thermal performance as the pitch size decreases.